Pengembangan Dashboard Admin menggunakan React JS dan Ant Design pada Toko Berkat - Pradipta, Rafael Deandra; Susetyo, Yeremia Alfa (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
The development of a web-based administrative dashboard for CV Berkat was conducted using the React JS framework and the Ant Design library. The application development process followed the waterfall method, ensuring that each phase, from requirements analysis to system maintenance, was fulfilled and completed systematically. This dashboard is designed to monitor sales data, product management, and employee reports with an attractive and interactive user interface. Based on testing result using Lighthouse, it was shown that the application performs more optimally when hosted compared to running locally, with assesment metrics such as Largest Contentful Paint (LCP) and Total Blocking Time (TBT) showing better results. The combination of React JS and Ant Design has proven to accelerate the development process thanks to the readily available components and support for the Single Page Application (SPA) method. Overall, this dashboard meets CV Berkat’s needs for real-time and efficient data monitoring while also facilitating future feature development.